Identity evaluation based entity cleansing for entities searched from linked open data cloud - Sohn, Yonglak (International Journal of Engineering and Technology, 2018)
Linked open data (LOD) cloud is composed of LODs that assert facts on an entity with various viewpoints. Knowledge expansion, hence, has been an important goal of LOD cloud and achieved by identity links, specified with <owl: sameAs> predicates, among entities in differ-ent LODs. After searching the LODs in depth through the identity links, an entity searched from surface LOD would be expanded with various facts obtained from the other LODs. This paper suggests how to evaluate the searched entities as identical to the entity of the surface LOD and then to pick out the entities whose identity levels were sufficiently high compared to the criteria specified in a user query. For entity identity evaluation, LODsâ€™ reputations and agreements on the identity assertions have been considered. Identity evaluation based enti-ty cleansing (IE2C) system and its surroundings have been implemented for experiments. Analysis on the experimental results presented that six or seven identity links would be necessary to an entity in order to achieve the goal of knowledge expansion. IE2C would provide in-depth searching results which were composed of trustworthy entities and their various descriptions to users. Â Â Â